Pt–Ru/Al2O3–C nanocomposites as direct methanol fuel cell catalysts for electrooxidation of methanol in acidic medium. Issue 113 (2nd November 2015) - Das, Suparna; Kundu, Patit P.
Abstract : We have employed different ratios of Al2 O3 and Vulcan carbon as supporting matrices for a Pt–Ru catalyst for direct methanol fuel cell catalysts. Abstract : The development of potential low cost anode catalyst–supporting matrix combinations for application in direct methanol fuel cells (DMFCs) has been an effective area of research till date, primarily due to the slower kinetics of the methanol oxidation reaction and poisoning of the catalyst by carbonaceous species. In this work, we have employed different ratios of Al2 O3 and Vulcan carbon ( i.e. Al2 O3 : Vulcan carbon (w/w) = 3 : 1, 2 : 1, 1 : 1) as supporting matrices for a Pt–Ru catalyst. Pt and Ru nanoparticles were deposited from a fixed amount of precursor salts H2 PtCl6 and RuCl3, respectively, by employing a NaBH4 reduction method at 80 °C. Pt–Ru/Al2 O3 –Vulcan carbon exhibited the highest catalytic activity when the weight ratio of Al2 O3 to Vulcan carbon was maintained at 2 : 1. This combination generated a peak current density of 399.6 μA cm −2 . Furthermore, the Pt–Ru/Al2 O3 –Vulcan carbon (2 : 1) catalyst system produced a current density of 148.92 mA cm −2 at +0.2 V and a maximum power density of 29.78 mW cm −2, using non-humidified air as the catholyte at 60 °C. However, when humidified air was used as the catholyte, a current density of 220.1 mA cm −2 at +0.2 V and a maximum power density of 44.02 mW cm −2 were obtained for the Pt–Ru/Al2 O3 –C (2 : 1) anode catalyst.